Host phenology and potential saprotrophism of ectomycorrhizal fungi in the boreal forest. (7th July 2016) - Hupperts, Stefan F.; Karst, Justine; Pritsch, Karin; Landhäusser, Simon M.
Summary: Phenology‐induced changes in carbon assimilation by trees may affect carbon stored in fine roots and as a consequence, alter carbon allocated to ectomycorrhizal fungi. Two competing models exist to explain carbon mobilization by ectomycorrhizal fungi. Under the 'saprotrophy model', decreased allocation of carbon may induce saprotrophic behaviour in ectomycorrhizal fungi, resulting in the decomposition of organic matter to mobilize carbon. Alternatively, under the 'nutrient acquisition model', decomposition may instead be driven by the acquisition of nutrients locked within soil organic matter compounds, with carbon mobilization a secondary process. We tested whether phenology‐induced shifts in carbon reserves of fine roots of aspen ( Populus tremuloides ) affect potential activity of four carbon‐compound degrading enzymes, β‐glucuronidase, β‐glucosidase, N ‐acetylglucosaminidase and laccase, by ectomycorrhizal fungi. Ectomycorrhizal roots from mature aspen were collected across eight stands in north‐eastern Alberta, Canada, and analysed during tree dormancy, leaf flush, full leaf expansion and leaf abscission. We predicted potential extracellular enzyme activity to be highest when root carbon reserves were lowest, should host phenology induce saprotrophism. Further, we anticipated enzyme activity to be mediated by invertase, a plant‐derived enzyme which makes carbon available to fungal symbionts in the plant–fungus interface. Root carbon reserves were positively correlated with invertase, suggesting phenology may affect carbon allocation to ectomycorrhizal fungi. However, of the four enzymes, host phenology had the largest effect on β‐glucuronidase, but activity of this enzyme was not correlated with root carbon reserves or invertase. Low‐biomass ectomycorrhizas had greater potential laccase activity than high‐biomass ectomycorrhizas, highlighting discrete functional traits in fungi for litter decomposition. Our results suggest that the decomposition of organic matter may be driven by foraging by fungi for nutrients locked within organic compounds rather than for mobilizing carbon. Furthermore, the potential ability to degrade lignin was more common in low‐biomass ectomycorrhizas when compared to high‐biomass ectomycorrhizas. A Lay Summary is available for this article. Abstract : Lay Summary